Fracture risk and mortality post‐kidney transplantation. (9th October 2015) - Ferro, Charles J.; Arnold, Julia; Bagnall, David; Ray, Daniel; Sharif, Adnan
Abstract: Background: Fractures are associated with high morbidity and economic costs. There is a paucity of information on fractures after kidney transplantation outside the United States. Methods: Data were obtained from the Hospital Episode Statistics database on kidney transplants performed in England between 2001 and 2013 and post‐transplant fracture‐related hospitalization. Mortality data were obtained from the Office for National Statistics. Results: In total, 21 769 first kidney transplant procedures were analyzed with 112 512 patient‐years follow‐up. Overall, 836 (3.8%) kidney allograft recipients developed a fracture requiring hospitalization. Event rate was 9.99 for any fracture and 1.54 for a hip fracture per 1000 patient‐years. Accounting for the competing risk of mortality, increasing age, female gender, white ethnicity, and a history of pre‐transplant diabetes mellitus or previous fracture were associated with increased fracture risk post‐kidney transplantation. Death occurred in 2407 (11.1%) kidney allograft recipients, with 173 deaths occurring post‐fracture. In an extended Cox model, hip fracture as a time‐varying factor was independently associated with an increased risk of death (hazard ratio, 3.288; 95% confidence intervals, 2.513–4.301; p < 0.001). Conclusions: Fracture rates in English kidney transplant recipients are lower than previously reported in US cohorts. Sustaining a hip fracture is associated with an increased mortality risk. Our results can be used to power future fracture prevention trials.